2006
DOI: 10.1002/cbf.1349
|View full text |Cite
|
Sign up to set email alerts
|

The effect of shock wave lithotripsy on nitric oxide and malondialdehyde levels in plasma and urine samples

Abstract: Shock wave lithotripsy (SWL) is accepted as the first treatment choice for most urinary stones, but it has adverse effects on the kidneys. The mechanisms underlying shock wave-induced renal injury have been discussed and include shear stress, thermal and cavitation effects and free radical formation. We investigated the effects of SWL on plasma and urinary nitrite, a stable metabolite of nitric oxide (NO), and malondialdehyde (MDA) concentrations. Between February and October 2004, 12 men and 8 women with rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…In our study, eNOS was significantly up-regulated 1 d after ESWA. The observation of increased eNOS levels after ESWA is in line with findings of other researchers [41][42][43]. In addition, we observed a significantly increased expression of vWF within the endothelial lining.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 93%
“…In our study, eNOS was significantly up-regulated 1 d after ESWA. The observation of increased eNOS levels after ESWA is in line with findings of other researchers [41][42][43]. In addition, we observed a significantly increased expression of vWF within the endothelial lining.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 93%
“…Bomanji et al [32] reported a decrease in renal perfusion after ESWL that was associated with the production of different OFRs. Aksoy et al [5] reported an increase in MDA and nitric oxide in plasma and urine immediately after a shockwave session. However, as in the present study, neither a study by Clark et al [33] nor a previous study [34] found changes in LPO levels.…”
Section: Eswl Associated Injurymentioning
confidence: 99%
“…The decrease in cytokines seen after administration (9) 70 (60) (4) (11) 150 (150) (9) 50 (80) (12) PG 90 (130) 120 (140) 210 (240) (5) 290 (220) (6) 80 (100) (7) β2-microglobulin, μg/L CoQ10 1904.67 (1120) 1480.9 (265) (2) (10) 1504 (569) (9) 1643 ( …”
Section: Effect Of Coq10 On Interleukinsmentioning
confidence: 99%
“…One of the possible mechanisms for SWL-related renal damage is increased oxidative stress due to renal ischemia-reperfusion injury (3,4,5). An experimental model on rabbits demonstrated a statistically significant decrease in tissue scavenger enzyme levels (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, long-term tissue effects of SWL are needed to be investigated despite its long-term proven efficacy. There have been several reports proposing that SWL causes oxidative stress due to renal ischemia-reperfusion injury (3,4,5). Furthermore, some agents have been tested to prevent SWL-induced renal oxidative stress (6,7).…”
Section: Introductionmentioning
confidence: 99%